Extension - Category C (ARQUISUR Revista, 2025)
Extension Award - Category CThe works nominated for the ARQUISUR Extension Award are those projects –whether they are in progress or executed-, whose impact can be verified, carried out by disciplinary and interdisciplinary teams made up of students, teachers and/or graduates, in order to allow the integration, articulation and strengthening of the different disciplinary areas of the Universities and developing various transferences to society of the scientific, technological and cultural knowledge, as a feedback system for academic activity.Category C  includes projects that involve assistance and/or technological transfer to the socio-productive environment.
Keywords: Arquisur Awards